ENTOTIC SOUND: DIAGNOSTIC PARALLELS - E. V. Kolpakova; S. A. Zhade; E. A. Kurinnaya; V. V. Tkachev; G. G. Muzlaev (Инновационная медицина Кубани)
We observed issues of etiology and pathogenesis, differentiatied diagnosis of entotic sound which is one of the frequent otoneurological complaints. Classification of this symptom is described.